Pengukuran Kesiapan Adopsi Teknologi Informasi Pada Poktan Hidup Baru Dengan Metode Digital Literacy Index - Az Zahra, Cindy Putri; Oktadini, Nabila Rizky; Sevtiyuni, Putri Eka; Marjusalinah, Anna Dwi; Akbaroka, Leo (Sekolah Sains Data, Matematika, dan Informatika. Institut Pertanian Bogor, 2024)
Although advances in digital technology offer great opportunities to improve efficiency and productivity in agricultural sector, its application has been uneven. Adoption of information technology still faces challenges, especially among farmers. This study aims to measure the readiness of information technology adoption in the Kelompok Tani (Poktan) Hidup Baru, Cempaka District, OKU Timur, using the Digital Literacy Index (DLI) which includes four main pillars such as Digital Skill, Digital Ethics, Digital Safety, and Digital Culture. The results show that farmers' digital literacy index has an average of 2.91, lower than the national average of 3.54. The biggest gap is in the digital skills pillar (2.20), signaling difficulties in operating devices. Meanwhile, digital ethics awareness is quite good (2.87). Education level (r = 0.79) and frequency of internet use (r = 0.97) have positive correlations with digital skills. However, the correlation between digital skills and digital safety was weak (r = 0.14), indicating a lack of understanding of cybersecurity. These findings emphasize the need to improve digital literacy to support technology adoption.